Nuclear Strategy of the DPRK in Modern Conditions - Anastasia Barannikova (Journal for Peace and Nuclear Disarmament, 2025)
The global shifts of recent years have not bypassed Northeast Asia, increasing the conflict potential of the region as a whole and the Korean peninsula in particular. As tensions grow, accompanied by a military buildup and tougher rhetoric, questions arise about the intentions and readiness of the Democratic People’s Republic of Korea (DPRK) to use nuclear weapons. The answer to this question should be sought not in official statements that are part of propaganda and information warfare, but through analyses of the country’s nuclear strategy. The present paper attempts to identify the real nuclear strategy of the DPRK based on analyses of the nuclear doctrine and trends in the development of the missile and nuclear program. The possible impact of regional changes on this strategy is also considered.